Предмет:
МатематикаАвтор:
анонимВычислим значение выражения (√18 - 4√3) * (√12 - √2).
Раскроем скобки и упростим выражение:
(√18 - 4√3) * (√12 - √2) = √18 * √12 - √18 * √2 - 4 * √3 * √12 + 4 * √3 * √2 = √(18 * 12) - √(18 * 2) - 4 * √(3 * 12) + 4 * √(3 * 2) = √9 * √(2 * 12) - √36 - 4 * √36 + 4 * √6 = 3 * √24 - 5 * √36 + 4 * √6 = 3 * √4 * √6 - 5 * 6 + 4 * √6 = 3 * 2 * √6 - 30 + 4 * √6 = 6 * √6 - 30 + 4 * √6 = 10 * √6 - 30.
Автор:
callie77Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть